Understanding Sexual Complaints and History Taking: A Standardized Patient Case on Dyspareunia for Obstetrics and Gynecology Clerkship Students - Jill M. Hagey; Jordan Toole; Kelly Branford; Tracey Reynolds; Elizabeth Livingston; Sarah K. Dotters-Katz (Association of American Medical Colleges, 2020)
Introduction Learning to elicit a sexual history and counsel patients on sexual pain aligns with the Association of Professors of Gynecology and Obstetrics clerkship objectives. This topic can be challenging to cover due to lack of exposure in clinical encounters and inadequate coverage in preclinical studies. Methods Second-year medical students in the OB/GYN clerkship participated in a standardized patient (SP) encounter on dyspareunia, receiving formative feedback on sexual history taking, differential diagnosis and management plan, and their SP's comfort during the encounter. Student feedback was obtained mid- and postclerkship. Summary statistics and regression models comparing SP encounter scores with shelf exam and clerkship scores are reported. Results From September 2018 through July 2019, 101 students completed the encounter. Students asked an average of 3.9 of 13 sexual history questions. Sixty-six percent of students identified a correct diagnosis; 48% provided a management plan. The majority of students were very good or excellent at creating a safe environment. Most reported the encounter enhanced their learning (62%) and identified knowledge gaps (72%). SP encounter score was not associated with shelf exam score or clerkship letter grade but was associated with final clerkship score (unadjusted ß = 0.2, p = .009; adjusted ß = 0.1, p = .2). A summary didactic session was developed following student feedback. Discussion This SP encounter and summary didactic session allowed students to improve their sexual history taking and may be associated with clerkship performance. These skills are necessary to advocate for patients with sensitive complaints across specialties.